The epic in the theatrical text Alarpi (Journal of the College of Basic Education, 2022)
Abdul Rahman Munif says that the participation of the audience in Wannous Theater revolves around the audience from (audienceA spectator to a participating audience, and thus he threw the fireball into the lap of everyone who was in the hall to leave a mark orA sign that that spectator carries outward - so that people can see their true self. 009One of the extremes in the epic is the declaration of the narrator participating in the event by identifying himself with the first person pronoun, as inThe play the question or (the story of the doctor Safwan bin Labib and what happened to him of the strange and strange) by Muhyi AbdHamid says:(I am Ahmed bin Sinan the porter; I am always under loads and burdens.. In my head is a headache that makes my life difficult...poisoned my life..and how often I thought of committing suicide to get rid of poverty and shame, if it weren't for the little ones..oh, what a pity thatEach one of us will have little onesMy Lord, oh my Lord, relieve me of some of the burden, and I shall return to him again.